A Real-Time Programmer's Tour of General-Purpose L4 Microkernels. (30th October 2007) - Ruocco, Sergio
Abstract : L4-embedded is a microkernel successfully deployed in mobile devices with soft real-time requirements. It now faces the challenges of tightly integrated systems, in which user interface, multimedia, OS, wireless protocols, and even software-defined radios must run on a single CPU. In this paper we discuss the pros and cons of L4-embedded for real-time systems design, focusing on the issues caused by the extreme speed optimisations it inherited from its general-purpose ancestors. Since these issues can be addressed with a minimal performance loss, we conclude that, overall, the design of real-time systems based on L4-embedded is possible, and facilitated by a number of design features unique to microkernels and the L4 family.